JPEG 2000 coding of textured parametric surfaces - Gamito, M. N.; Dias, J. (Proc. SPIE 5308, Visual Communications and Image Processing 2004, 2004)
Paper Abstract JPEG 2000 is a flexible standard for coding many different types of images. This flexibility will be increased in the near future with the JP3D standard, an extension of JPEG 2000 to three dimensions. This paper presents a set of techniques to code three-dimensional textured parametric surfaces, common in Computer Graphics applications, using JPEG 2000 and possibly extensions from the newer JP3D standard. These coding techniques generate compressed files of much smaller sizes than conventional file formats for storing three-dimensional objects. This is because the proposed coding techniques can exploit the strong correlation that exists between neighbouring surface points in a parametric representation. Furthermore, it is possible to encode parametric surfaces which change through time, something that is not available in many conventional file formats. The reversible compression mode of JPEG 2000 ensures that three-dimensional surfaces can be recovered without error after decompression. This is an important requirement for surfaces used in medical imaging, for example. This paper will demonstrate how a large variety of surfaces can be coded with JPEG 2000. The techniques presented here impose only one but important constraint on the surfaces: they must obey a parametric representation.